1993
DOI: 10.1007/bf03392617
|View full text |Cite
|
Sign up to set email alerts
|

Mands Across the Water: A Report on the Application of the Picture-Exchange Communication System in Peru

Abstract: We thank Liliana Mayo and Judith LeBlanc for their feedback on an earlier draft ofthis manuscript. We also express our gratitude to them for their efforts to bring us to Peru. Our appreciation is extended to the staff of the Ann Sullivan Center, especially for their efforts to integrate us into their "family." We thank the parents and the students of the Center for their warmth and generosity of spirit. Finally, we thank the Christina School District for their support of our efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 3 publications
0
57
0
1
Order By: Relevance
“…The symbols or pictures may be used in an exchange of cards (PECS) (Bondy et al 1993) or by simply pointing at an image that may accompany a word, phrase or referent that best suits the user's needs. Systems can include the alphabet when the user is literate and have other abstract symbols to represent parts of speech, tenses and additional elements in speech.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The symbols or pictures may be used in an exchange of cards (PECS) (Bondy et al 1993) or by simply pointing at an image that may accompany a word, phrase or referent that best suits the user's needs. Systems can include the alphabet when the user is literate and have other abstract symbols to represent parts of speech, tenses and additional elements in speech.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Considerable research has identified the effectiveness of tokens, points, gold stars, and the like in achieving this purpose (Kazdin, 1982;Kazdin & Bootzin, 1972), yet the identification of less contrived, more naturally occurring conditioned reinforcers will be useful for ensuring generalization to other settings. Pictures of a desired object, edible item, or activity may serve a similarly useful purpose when presented during a delay, particularly if the pictures are being used concomitantly in a communication teaching program (e.g., Bondy & Frost, 1993). Conditioned reinforcers might also be verbal in nature (Hayes & Hayes, 1993).…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%
“…Functional communication training (Carr & Durand, 1985;Durand & Carr, 1991) might serve as a means by which individuals can produce their own conditioned reinforcers as well. Teaching an individual to mand desired items using chosen pictures may allow the pictures to acquire conditioned reinforcing properties when the specified reinforcer is made available at the end of the delay (Bondy & Frost, 1993).…”
Section: Basic Research Related To Delayed Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-referencing of the terms gives rise to linkages that suggest areas of fruitful empirical study (e.g., relations among coding, tacting, and remembering), and other potentially productive linkages are implied (e.g., relations among equivalence, intraverbal behavior, and verbal learning; adduction, abstraction, productivity, and recombinatory generalization). Research ideas also may be derived from (a) recent theoretical discussions about the role of verbal behavior in stimulus class formation and other complex behaviors (e.g., Horne & Lowe, 1996;Stromer et al, 1996), (b) renewed interest in interventions that concentrate on the function of verbal behavior rather than its structure (e.g., Charlop-Christy & LeBlanc, 1999), and (c) the development of specialized language interventions and broad curricula based on Skinner's ideas (e.g., Bondy & Frost, 1993;Brady et al, 1994;Shafer, 1994;Sundberg & Partington, 1998).…”
Section: Verbal and Social Behaviormentioning
confidence: 99%